2021
DOI: 10.1111/lam.13523
|View full text |Cite
|
Sign up to set email alerts
|

Functional group characterization of lactic bacterial biosurfactants and evaluation of antagonistic actions against clinical isolates of methicillin‐resistant Staphylococcus aureus

Abstract: The present study investigated the antimicrobial and antibiofilm potential of biosurfactants derived from Lactobacillus fermentum Lf1, L. fermentum LbS4 and Lactobacillus plantarum A5 against clinical isolates of methicillin‐resistant Staphylococcus aureus (MRSA). The cell wall‐bound and intracellular biosurfactants were extracted by solvent extraction method. Fourier‐transform infrared spectroscopy‐based characterization of biosurfactants revealed the heterogeneous chemical composition involving proteins, fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…27 The bacteriostatic effect of the fermentation supernatant of LAB mainly comes from the lactic acid and SCFA such as acetate, propionate, and butyrate, creating an unfavorable acidic environment for invading pathogens. 28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo , indicating that they can metabolize and produce bacteriostatic substances.…”
Section: Discussionmentioning
confidence: 99%
“…27 The bacteriostatic effect of the fermentation supernatant of LAB mainly comes from the lactic acid and SCFA such as acetate, propionate, and butyrate, creating an unfavorable acidic environment for invading pathogens. 28 L. fermentum and L. gasseri can release anti-microbial agents such as bacteriocins, 29,30 biosurfactant 31,32 and hydrogen peroxide. 33,34 In line with this, our results showed that LF23 and LG80 fermentation supernatants could significantly inhibit the growth of H. pylori and reduce H. pylori infection in vivo , indicating that they can metabolize and produce bacteriostatic substances.…”
Section: Discussionmentioning
confidence: 99%
“…BS is a compound that exhibits amphiphilic properties and is produced by a variety of microorganisms [89]. It is classified as a secondary metabolite of microorganisms and encompasses a range of structural groups, such as glycolipids, polysaccharide-lipid complexes, lipoprotein-lipopeptides, and phospholipids.…”
Section: Reduction In Surface Adhesionmentioning
confidence: 99%
“…Among Lactobacillaceae, Lactiplantibacillus plantarum was the most frequently reported species, with 36 instances of growth inhibiting, bactericidal, or anti-biofilm properties against at least one ESKAPEE pathogen . Lactobacillus fermentum [21,22,28,30,31,43,[55][56][57][58][59][60][61][62][63][64][65] and Lacticaseibacillus rhamnosus [19,21,25,27,31,[66][67][68][69][70][71][72][73][74][75][76][77] were both reported 17 times, Lactobacillus acidophilus was reported 16 times [21,28,55,67,[78][79][80][81][82][83][84][85][86][87][88]…”
Section: Species Reported To Suppress Eskapee Pathogen Growthmentioning
confidence: 99%